Qualitative study exploring the views and perceptions of parents/carers of young children with CF regarding the introduction of CFTR modulator therapy (The REVEAL study; PaRents pErspectiVEs of KAftrio in chiLdren aged 2–5) - Kevin W Southern; Sioned Haf Davies; Faye Wade; Heather Fogg; Adam Walsh (BMJ Open Respiratory Research)
Background Cystic fibrosis (CF) is associated with a historically high treatment burden which causes anxiety and exhaustion for parents of children with CF, especially in the early years of a child’s life. Recently, a new medication, elexacaftor/tezacaftor/ivacaftor (ETI), has become available to some people with CF, which has had a significant impact on the quality of life of older children and adults. This medication will soon be available for children ages 2–5 in the UK. This study investigated parents’ perspectives before their children could start ETI.Method 10 parents of young children with CF participated in semistructured online focus groups. The data were analysed using thematic analysis to identify key themes.Results Three reviewers identified four main themes: (1) The ‘roller coaster’ of parental emotions: Shock, hope, uncertainty and anticipation, (2) The dark side of the unknown, side effects and burden of decision making, (3) The value of simple pleasures in a life with CF; treatment burden, normality, future, family life and (4) Reforming clinical care in the new era of CF care; support, communication and the future.Conclusion Parents experience a range of emotions from the day of diagnosis. While ETI brings hope and positivity, parents are concerned about the medication’s safety. Parents have clear hopes and wishes for their child’s future and reflect on the need for clinicians to consider reforming clinical care in the new era of CF for those eligible for new therapies.